The effect of shredded paper as partial sand replacement on properties of cement sand brick - Solahuddin, Azuwa (2017)
Cement sand brick is type of brick made from a mixture of cement, sand and water. The wastage of paper in industry for every year is increasing gradually. Shredded paper was dumped as waste behind the mill or landfill and causes environmental pollution. Sand mining causes bank erosion, water pollution, coastal destructions, air pollution and destruction of flora and fauna. Utilizing shredded paper as partial sand replacement in producing cement sand brick would reduce the environmental pollution. The objectives of study are to investigate the effect of shredded paper as partial sand replacement on compressive strength, flexural strength, and water absorption of cement sand brick. All the specimen were subjected to water curing at 7, 14 and 28 days. The finding shows that cement sand brick containing 20% shredded paper replacement exhibit the highest compressive strength and flexural strength value. This study shows that shredded paper can be used as a partial sand replacement material in cement sand brick production.